PEMBANGUNAN WILAYAH KECAMATAN BERBASIS KOMODITAS PERTANIAN DI KABUPATEN GUNUNGKIDUL PROPINSI DAERAH ISTIMEWA YOGYAKARTA (AGRICULTURE COMMODITY-BASED SUB-DISTRICT DEVELOPMENT IN GUNUNGKIDUL, YOGYAKARTA) - Ropingi, Ropingi; Sudartono, Yanwar (Jurnal Ilmu-Ilmu Pertanian, 2008)
The aims of this research were (1) to identify the pre-eminent agriculture commodity, (2) to know the role of pre-eminent commoditiy in regional economics based on income surplus and income multiplier, (3) to know specialization and localization of pre-eminent agriculture commodity, and (4) to identify the priority of pre-eminent agriculture comodity development in Gunungkidul Regency. The basic method that be used in this research is descriptive method, with the research is taken purposively. The data analysis used Location Quotient (LQ), Income Surplus and Income Multiplier, Specialization Quotient (KS) and Localization Quotient (Lo). The data used production data of commodity and the average price data of commodity during one year. The result of the research are (i) indicate that the pre-eminent agriculture commodity which is laboured in most of subdistrict in Gunungkidul Regency are gogo paddy, cassava, maize, soy, sweet potato, petai, coconut, tobacco, kapok randu, cow, goat, teakwood, goldfish, mujair fish, freshwater catfish, manyung fish, cucut fish, lobster and seaweeds. (ii) Income Surplus in Gunungkidul Regency has positive value that is equal to Rp 85.746.879.164,14. Multiplier income in Gunungkidul Regency is equal to Rp 1,5468. (iii) Based on Specialization Quotient and Localization Quotient analysis, gogo paddy and cassava is known as a specialized commodity in Gunungkidul Regency, from 18 subdistricts in Gunungkidul Regency, there are 17 subdistricts has a concentration to certain agricultural activity, while from 92 pre-eminent agriculture commodities in Gunungkidul Regency, 66 commodities are concentrated in certain subdistrict and 26 commodities spread in several subdistricts. (iv) The pre-eminent agriculture commodity which priority to be developed in Gunungkidul Regency are sonokeling tree in Gedangsari Subdistrict, durian in Pathuk Subdistrict, markisa in Ngawen Subdistrict, black stromateus fish in Panggang Subdistrict, and cardamom in Purwosari Subdistrict.